An Efficient Synthesis of 4(5)-Benzyl-l-histidines Employing Catalytic Transfer Hydrogenolysis at Elevated Temperatures - Smith, D. David; Gallagher, Audrey T.; Crowley, Vincent M.; Gergens, Wayne M.; Abel, Peter W.; Hulce, Martin (Synthesis, 2014)
An efficient two-step synthesis of 4(5)-benzyl-l-histidine from l-histidine was developed. A Pictet–Spengler reaction between l-histidine and benzaldehyde in the presence of excess strong base yielded 4-l-phenylspinacine within one hour. Catalytic transfer hydrogenolysis in methanol at reflux using ammonium formate rapidly converted 4-l-phenylspinacine to 4(5)-benzyl-l-histidine within five minutes. No racemization of the final product 4(5)-benzyl-l-histidine was observed using the Marfey reagent. To show the utility of this method, a series of fluorinated benzylhistidines were prepared.
Keywords: amino acids; benzylation; Pictet–Spengler reaction; catalytic transfer hydrogenolysis; electrophilic aromatic substitution